Potency of Catfish (Clarias sp.) Protein Hydrolysates as Candidates Matrices for Microbiology Reference Material - Kurniawati, Eti; Ibrahim, Bustami; Desniar, Desniar (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2019)
Fish protein hydrolysate (FPH) is a derivative product of fish proteins containing smaller peptides and amino acids. FPH products have high water solubility, good emulsion capacity, and large expanding ability. With its functional properties, it allows FPH to be used as a raw material in the manufacturing of secondary microbiological reference materials. This study was intended to characterize catfish (Clarias sp.) FPH as a candidate for the matrix of microbial secondary reference. The FPH was prepared through enzymatic hydrolysis, freeze-drying and milling. The hydrolysis processes were carried out using 5% (w/w) papain, 55 °C for 5 hours, then the papain activity was stopped by increasing the temperature to 80 °C for 20 minutes.The FPH was combined with gelatine, sodium glutamate, glucose solution, and was spiked with Salmonella enteritica sv Enteritidis and freeze-dried. Results showed that catfish FPH was yellowish-white powder with a FPH yield of 11.05%. The proximate analysis of FPH revealed the moisture content of 3.77 ± 0.12%, ash content of 7.26 ± 0.03%, protein content of 86.09 ± 0.17%, and fat content of 1.38 ± 0.07%. The protein content of the FPH was greater than skim milk (33.42%). Carbohydrate levels of catfish FPH and skim milk were 1.56% and 57.46%, respectively. The best concentration of catfish FPH to perform as a microbiological reference material was 14%, obtained from highest viability of Salmonella bacteria and homogeny. The candidate for reference material were stable at storage temperatures of -20 oC.